Building Optimisation Vis-À-Vis Solar Shading for Improved Comfort and Energy Efficiency in Classrooms - Mark Alegbe; Lawrence Chukwuemeka; John Lekwauwa Kalu; Amaka Eke-Nwachukwu (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2023)
Excessive solar radiation negatively affects classroom occupants' performance and thermal comfort, especially in buildings with West and East-facing glazed openings. This study utilises fixed external shading devices and triple-glazed low-emissivity windows to optimise a classroom building in Nigeria. Employing hybrid ventilation mode in EnergyPlus simulations, the optimised model shows a 44% reduction in discomfort hours, a 23% decrease in cooling load, and a 16% drop in energy demand compared to the original design. Comparative analysis of the optimised model with the as-built and West-East oriented classroom reveals a 16% and 10% reduction in energy consumption per conditioned area, along with 56 KWh/m² and 32 KWh/m² savings in cooling demand, respectively. Despite the effectiveness of fixed shading in curbing solar gains, occasional glare persists. This research underscores that shading alone may not fully meet thermal comfort requirements, emphasising the importance of building fabrics, building orientation and climate-sensitive design.